2007
DOI: 10.1063/1.2730501
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption of gaseous ClCS detected with time-resolved Fourier-transform spectroscopy

Abstract: A transient infrared absorption spectrum of gaseous ClCS was detected with a step-scan Fourier-transform spectrometer coupled with a multipass absorption cell. ClCS was produced upon irradiating a flowing mixture of Cl2CS and N2 or CO2 with a KrF excimer laser at 248 nm. A transient band in the region of 1160-1220 cm-1, which diminished on prolonged reaction, is assigned to the C-S stretching (nu1) mode of ClCS. Calculations with density-functional theory (B3P86 and B3LYP/aug-cc-pVTZ) predict the geometry, vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…19,[30][31][32][33][34][35] The White cell, with a volume ϳ1600 cm 3 , accommodates two rectangular quartz windows to pass photolysis beams that propagate perpendicularly to multipassing IR beams. 19,[30][31][32][33][34][35] The White cell, with a volume ϳ1600 cm 3 , accommodates two rectangular quartz windows to pass photolysis beams that propagate perpendicularly to multipassing IR beams.…”
Section: Methodsmentioning
confidence: 99%
“…19,[30][31][32][33][34][35] The White cell, with a volume ϳ1600 cm 3 , accommodates two rectangular quartz windows to pass photolysis beams that propagate perpendicularly to multipassing IR beams. 19,[30][31][32][33][34][35] The White cell, with a volume ϳ1600 cm 3 , accommodates two rectangular quartz windows to pass photolysis beams that propagate perpendicularly to multipassing IR beams.…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that, on coupling a step-scan Fourier-transform infrared (FTIR) spectrometer with a multipass absorption cell, temporally resolved IR absorption spectra of gaseous reaction intermediates such as ClCO, 18 ClSO, 19 CH 3 SO 2 , 20 C 6 H 5 SO 2 , 21 ClCS, 22 CH 3 OO, 23 ClCOOH, 24 CH 3 C(O)OO, 25 CH 3 SO, and CH 3 SOO (Ref. 26) were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…The further oxidation of sulfur in SCCl 2 produces SO 2 , , with the remaining part eventually expected to form CO 2 and HCl. Alternatively, we have also revealed that the abstraction of Cl by H or other radicals may convert SCCl 2 to CS , which itself is crucial in the formation of CS 2 . In the case of folpet, the latter fate of SCCl 2 is limited by the lower availability of H, as evidenced by the lower yields of CS 2 in comparison with those from captan.…”
Section: Resultsmentioning
confidence: 80%
“…In the structure of folpet, H atoms on the aromatic ring are more strongly bonded than those on the cyclohexene ring of captan. To estimate a rate constant for abstraction of H by O 2 from the aromatic ring, we adopt the experimental rate constant for abstraction of H by O 2 from benzene to form HO 2 of 6 × 10 13 exp (−60 kcal mol −1 / RT ) cm 3 mol −1 s −1 . Under the O 2 level of this study (6.0 mol %), the rate of the bimolecular reaction would be approximately 7 × 10 7 exp (−60 kcal mol −1 / RT ) cm 3 mol −1 [folpet] s −1 .…”
Section: Resultsmentioning
confidence: 99%